YY1-induced DDX18 modulates EMT via the AKT/mTOR pathway in esophageal cancer: a novel therapeutic target - Xiaochao Ma; Yulu He; Yue Yang; Tianyu Lu; Ze Tang; Youbin Cui; Rui Wang (Journal of Translational Medicine)
Abstract Background Esophageal cancer is the 11th most common malignancy and the 7th leading cause of cancer-related death globally. Identifying key molecules and underlying mechanisms in the progression of esophageal cancer represents an effective strategy for developing novel therapeutic approaches. Methods DDX18 expression in clinical specimens was evaluated by immunohistochemistry and western blot analysis. Functional assays were performed in cells with either DDX18 knockdown or overexpression. Dual luciferase reporter assays and chromatin immunoprecipitation (ChIP) were conducted to validate the interaction between YY1 and the DDX18 promoter. A xenograft tumor model was utilized to investigate the role of DDX18 in vivo in esophageal cancer. Results DDX18 was found to be markedly overexpressed in esophageal cancer, with its levels significantly higher in patients with pathological grade III compared to those with grades I–II. In vitro, DDX18 enhanced cell proliferation, migration, and invasion, while concurrently suppressing apoptosis. Furthermore, DDX18 promoted epithelial–mesenchymal transition (EMT) and activated the AKT/mTOR signaling pathway. The use of AKT inhibitors effectively abrogated the oncogenic effects of DDX18. Dual luciferase and ChIP assays confirmed that YY1 binds to and stimulates DDX18 transcription. In rescue experiments, YY1 countered the inhibitory effects of DDX18 knockdown on cell proliferation, EMT, and AKT/mTOR activation. In vivo, DDX18 knockdown resulted in reduced tumor growth. Conclusions The transcription of DDX18 was activated by YY1, and DDX18 promoted tumor cell growth and EMT through the AKT/mTOR signaling pathway in esophageal cancer cells.